INFORMED CONSENT DOCUMENTS: RECOMMENDATIONS TO ENHANCE PARTICIPANT COMPREHENSION - Ulderich, Tracy (My University, 2008)
The purpose of this research was to determine if current government recommendations to enhance participant comprehension of information presented in Informed Consent Documents (ICDs) are effective. One-hundred and eighty four volunteers were asked to complete a survey of successive documents which included a pre-questionnaire, an ICD, a demographics questionnaire, a reading comprehension test, and a post-questionnaire. Results from one ICD written below the eighth grade level and one visually modified ICD were compared to an unmodified ICD. The participants reading of a Grade Level ICD showed a statistically different increase in comprehension over the unmodified ICD. The data suggests that writing an ICD at lower grade levels may increase participant comprehension but does not effectively increase document readability. Furthermore, the data also implicates that visual changes tested in this research did not increase comprehension or readability of the selected ICD. Overall comprehension, as measured by a modified Deaconess Informed Consent Comprehension Test (DICCT), for all documents was poor and participant perception, as measured by a modified Informed Consent Aggregate Score (ICAS), for each of the respective ICDs was not statistically different. The general ineffectiveness of all three documents used in this survey to convey critical information suggests that changes or additions to the regulations on Informed Consent (IC) need to be made to increase the effectiveness of ICDs.